Study on the separation and thin film deposition of tarry aromatics mixtures (soot extract and naphthalene pitch) by high-vacuum heating. (1st December 2017) - Apicella, B.; Tregrossi, A.; Popa, C.; Mennella, V.; Ciajolo, A.; Russo, C.
Graphical abstract: Highlights: Pre-separation of tarry materials for their deeper characterization. Insights on tar and pitch structure for guiding the production of tailored carbon materials. Understanding of composition and structures of tars and pitches. Combination of advantages and shortcomings of chemical and spectroscopic techniques. Inferring the self-organization of tars and pitches derived thin films. Abstract: Tarry mixtures derived from coal and heavy fuel processing, organic synthesis or formed in combustion systems are complex mixtures of organic, mainly aromatic, species with molecular weight spanning from few hundreds up to thousands of mass units. Many different diagnostics are required for their characterization, nevertheless the speciation of the huge number of aromatic molecules is only partially effective, avoiding reaching the complete map of the tar composition. Understanding of composition and structures of tars from different sources and processes would lead to a greater comprehension of their possible transformation in carbons relevant in combustion and environmental fields as well as for material production. To this regard, the pre-separation in lighter and heavier fractions simplifies the further characterization of tar composition. In the present work a fractionation method based on moderate heating in high-vacuum conditions (10 −6  mbar) was tested on a synthetic naphthalene pitch and on a flame-formed tar, typically extracted from soot (soot extract), getting information on the components distribution and characteristics by means of chromatography, mass spectrometry and spectroscopy. Although the fractionation of light and heavy PAH components was not thorough even in the case of soot extract, the method appeared successful in separating tars in classes with narrower MW distribution, allowing to get further insights on their characterization. The lighter components obtained by condensation/deposition as thin films were analyzed by polarized light microscopy to infer their self-organization in cluster assembly and/or crystal forms.